The Implementation Evaluation of Drug Demand Plan in Pharmacy Installations of Dr Fauziah Hospital Bireuen Aceh Province - Intan Sari; Asriwati Asriwati; Vivi Eulis Diana (Newinera Publisher, 2022)
Pharmaceutical services are direct and responsible services to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the quality of life of patients. The unavailability of drugs at the Pharmacy Installation is usually caused by delays in the arrival of drugs after they are ordered because its stock is empty at the distributor. The purpose of this study was to analyze the planned need for drugs that were lacking in the Pharmacy Installation at Dr. Fauziah Hospital Bireuen Regency, Aceh Province in 2021. The research used qualitative design. Characteristics of key informants were Head of Pharmacy Installation, Person in Charge of Pharmaceutical Supplies, Responsible for Pharmacy Warehouse, Responsible for Outpatient Distribution, Responsible for Inpatient Distribution, Pharmacy Installation Administration Officer, Pharmacy Officer, Distributor Officer, while the main informants were employees. Data collection technique was done by using the Triangulation method. Data analysis used descriptive qualitative with data triangulation stages of technique, source and time.The results of the study showed that planning was done by a planning team that had been formed. The drug procurement process more often used the ordering consumption method based on the e-catalog. In the distribution process, it was done by direct distribution.It is expected that it is necessary to improve the Pharmacy Installation of Dr. Fauziah Hospital Bireuen Regency. The Installation party should further improve the Management Information System (SIM) in queuing drug data.